Tradisi "Tena Ladja' Masyarakat Penangkap Ikan Paus di Lamalera, Flores Timur - Lelaona, Yohanes Antonius (Perspektif, 2011)
This article describes the fishing tradition (berperahu or tena ladja) in Lamalera, a village on the south coast of Lembata island, East Flores. Fisherfolk of Lamalera is known for their traditional whale hunting. The primary data for this article comes from the narratives gathered by the author during his vacation in the village. The author also uses secondary data from written sources. After de- scribing their traditional whaling practices and the vital and noble values be- hind these practices, the author proposes that the government should declare the tena ladja tradition as a national cultural heritage (cagar budaya nasional) to avoid its demise under the wave of modern mindset to adopt modern values and technology.